2014
DOI: 10.11646/zootaxa.3765.4.2
|View full text |Cite
|
Sign up to set email alerts
|

<p class="HeadingRunIn"><strong>The high-level classification of skinks (Reptilia, Squamata, Scincomorpha)</strong></p>

S. BLAIR HEDGES

Abstract: Skinks are usually grouped in a single family, Scincidae (1,579 species) representing one-quarter of all lizard species. Other large lizard families, such as Gekkonidae (s.l.) and Iguanidae (s.l.), have been partitioned into multiple families in recent years, based mainly on evidence from molecular phylogenies. Subfamilies and informal suprageneric groups have been used for skinks, defined by morphological traits and supported increasingly by molecular phylogenies. Recently, a seven-family classification for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 53 publications
2
53
0
Order By: Relevance
“…The taxonomy of skinks follows the proposal of Hedges (), which for the most part is supported by the results of Pyron et al (). Hedges () proposed a taxonomic revision of skinks, elevating the three subfamilies within Scincidae to superfamilies (Acontoidea, Scincoidea, and Lygosomoidea) and also recognizing nine families: Acontidae, Scincidae, Ateuchosauridae, Egerniidae, Eugongylidae, Lygosomidae, Mabuyidae, Ristellidae, and Sphenomorphidae. One exception is Ablepharus which is listed as an eugongylid in Hedges (), but see other authors, e.g.…”
Section: Methodssupporting
confidence: 63%
See 1 more Smart Citation
“…The taxonomy of skinks follows the proposal of Hedges (), which for the most part is supported by the results of Pyron et al (). Hedges () proposed a taxonomic revision of skinks, elevating the three subfamilies within Scincidae to superfamilies (Acontoidea, Scincoidea, and Lygosomoidea) and also recognizing nine families: Acontidae, Scincidae, Ateuchosauridae, Egerniidae, Eugongylidae, Lygosomidae, Mabuyidae, Ristellidae, and Sphenomorphidae. One exception is Ablepharus which is listed as an eugongylid in Hedges (), but see other authors, e.g.…”
Section: Methodssupporting
confidence: 63%
“…The occipital shield of parietal ZIN PH 265/181 is absent and this anatomical feature is almost a rule in non‐lacertid scincomorphans (Borsuk‐Białynicka et al, ). Herein, selected Scincomorpha members ( sensu Hedges, ) and an outgroup are studied for comparison (Fig. ) and pictured in Figures .…”
Section: Discussionmentioning
confidence: 99%
“…There are currently 154 genera and 1,602 species assigned to the Family Scincidae (Uetz and Hošek, 2015, but see Hedges, 2014 for an alternative arrangement). Several studies have revealed concealed genetic divergence in multiple lineages of skinks from different regions of the world (Daniels et al, 2009; Engelbrecht et al, 2013; Heideman et al, 2011; Portik et al, 2011; Siler et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Continued use of skull morphology also supported the separation of the family Scincidae into four subfamilies: Acontinae, Feylininae, Lygosominae, and Scincinae (Greer, 1970). Recent molecular and morphological evidence (Skinner et al, 2011; Hedges and Conn, 2012; Hedges, 2014) suggested skinks could be divided into as many as nine families. Although considered controversial, ignored or rejected by subsequent authors (e.g., Pyron et al, 2013; Lambert et al, 2015; Linkem et al, in press), this new subdivision continues to support skinks as a monophyletic group (Hedges, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation